UMP named Best University in Research and Innovation for Non-Research University - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP) was named best university in research and innovation under the category of Research and Innovation Excellence (Institution) for Non-Research University at the recent Malaysia’s Research Star Award (MRSA) 2019 and CRÈME 2019 Acknowledgement of Journal Award.